Three Complementary Sampling Approaches Provide Comprehensive Characterization of Pesticide Contamination in Urban Stormwater - Gab Izma; Melanie Raby; Justin B. Renaud; Mark Sumarah; Paul Helm; Daniel McIsaac; Ryan Prosser; Rebecca Rooney (Urban Science, 2025)
Urban areas are expanding rapidly and experience diverse and complex contamination of their surface waters. Addressing these issues requires different tools to describe exposures and predict toxicological risk to exposed biota. We surveyed 21 stormwater management ponds in Brampton, Ontario using three types of sampling methods deployed concurrently: time-integrated water sampling, biofilms cultured on artificial substrates, and organic-diffusive gradients in thin films (o-DGT) passive samplers. Our objective was to compare pesticide occurrences and concentrations to inform monitoring in stormwater ponds, which reflect pesticide pollution in urban areas. We detected 82 pesticides across the three sampling matrices, with most detections occurring in o-DGT samplers. The in situ accumulation of pesticides in o-DGTs during deployment and the high analytical sensitivity achieved establishes o-DGTs as excellent tools for capturing the mixtures of pesticides present. Water and biofilm sampling demonstrated that pesticide concentrations available for uptake are relatively low, with most below toxicological thresholds. Yet our results demonstrate that urban areas are subject to a wide range of pesticides, including herbicides, insecticides, and fungicides, and underscores the urgency of research to quantify the risks of chronic exposure to this chemical mixture.